Enhancement of the Performance of Junior High School Students using Numeracy Mobile Game on Operations of Integers - Lopez, Lydia Marie R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to evaluate and validate the developed numeracy mobile game to help improve the performance of junior high school students on the operations of integers in a public national high school in Antipolo City, the Philippines. The researcher used experimental and descriptive research designs in the study. The sources of data in this research were eighty (80) JHS students, twenty (20) from each grade level, from Old Boso-Boso National High School. Other respondents were the forty (40) teacher respondents consisting of twenty (20) experts and twenty (20) math teachers from Schools Division of Antipolo. The statistical tools used in this study were the frequency, percentage, weighted mean, independent-samples t-test, and paired t-test. It was revealed that there was no significant difference between the evaluations of the two groups of respondents on the developed numeracy mobile game in operations of integers in terms of game mechanics, visual aesthetic design, narrative design, incentive system, musical scores, and content and skills. It is recommended that the user interface of the game needs some enhancements like the controls for arrows up and down and improve the tutorial part before starting the real game or at the start of every level.